Investigating Faculty Perceptions of Creating and Enhancing Accessible Online Courses with Ally - Patrick R. Lowenthal; Christopher Prokes; Amy Lomellini; Crystal Gasell (Open Praxis)
As online education grows, ensuring accessibility for diverse and marginalized learners has become increasingly critical. This study investigated faculty perceptions of Anthology Ally, a tool designed to enhance the accessibility of online course materials by identifying and resolving accessibility issues. Using survey data from 78 educators at two- and four-year institutions, the research explores faculty knowledge, usage patterns, and attitudes toward Ally, alongside their perspectives on the responsibility for creating accessible online courses. Results reveal that most faculty view Ally as an effective, user-friendly tool that supports accessible content creation and improves student learning experiences. Faculty highlighted Ally’s ability to provide alternative formats, offering students flexibility and addressing diverse needs. However, challenges persist, including the time required to use the tool, usability limitations, and insufficient training. The study also identifies a lack of consensus on responsibility for accessibility, with faculty often viewed as the primary drivers supported by instructional designers and other institutional staff. Findings suggest the need for a collaborative, institution-wide approach to accessibility, emphasizing proactive course design, continuous training, and a cultural shift from compliance-driven practices to equity-focused strategies. These insights provide a foundation for developing effective policies and practices prioritizing inclusivity and equitable online learning access.